Economic analysis of the Nairobi Cancer Registry: Implications for expanding and enhancing cancer registration in Kenya. (December 2016) - Korir, Anne; Gakunga, Robai; Subramanian, Sujha; Okerosi, Nathan; Chesumbai, Gladys; Edwards, Patrick; Tangka, Florence; Joseph, Rachael; Buziba, Nathan; Rono, Victor; Parkin, Donald Maxwell; Saraiya, Mona
Highlights: Cost data was collected from Nairobi Cancer Registry for two annual periods. Substantial cost variation existed between the two annual periods. Cost data helps justify the need for continuous funding for registry operations. Abstract: Introduction: Cancer registration is an important activity for informing cancer control activities. Cancer registries in Sub-Saharan Africa have limited resources to effectively operate because of competing priorities. To date, there has not been an assessment of the resources and funding needed to perform all the activities essential for cancer registration in Kenya. Evidence will help registries to quantify and advocate for the funds needed to sustain, enhance, and expand high quality cancer registration in Kenya. Methods: In this study, we used the Centers for Disease Control and Prevention's (CDC's) International Registry Costing Tool ( IntRegCosting Tool ) to evaluate the funding, cost, and labor resources used to perform the cancer registry operations in Nairobi County for two annual periods between July 2012 and June 2014. Results: Funding from grants, research studies, and international organizations provided 70% of the registry operations' cost. For both time periods, the most-costly registry activities were related to administration, management, and training, along with data acquisition activities such as data abstraction, entry, and validation. Even among these core registry activities, however, substantial variations existed. Conclusions: Stable funding for cancer registry operations is necessary to sustain core registry activities in other to deliver high-quality data, which in turn is necessary to foster evidence-based policies to improve cancer outcomes. As stakeholders look into expanding the Nairobi Cancer Registry into a national program, the cost data provided in this study will help justify the funding required for sustaining and expanding registry activities.